A molybdenum alloy and a method of making the same
Patent Information
- Application Number
- CN202610712105.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2046-05-22
AI Technical Summary
[0004]基于国内传统市售ODS钼合金(如钼镧、钼锆合金)应用瓶颈的深入分析,其在高温抗氧化性、室温韧性、高纯净度、加工性、焊接性及产品质量一致性方面存在显著短板,严重限制了其在电子、半导体、核能等尖端领域的可靠性与应用范围
[0033]一方面,本发明实施例提供一种钼合金,其中,按质量百分比计,所述钼合金包括以下化学成分:稀土Y:0.20wt%-0.30wt%,Zr:0.12wt%-0.20wt%,W:0.20wt%-0.30wt%,余量为Mo及不可避免的杂质。在此,本发明实施例通过上述成分设计,调控第二相尺寸及分布,引入与基体形成共格/半共格的稀土复合氧化物,同步实现细化晶粒,净化晶界的效果,可成功制备具有复合强化效果的高性能(优异的强度和塑性)钼合金。
Smart Images

Figure CN122235553B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder metallurgy nanostructure materials technology, and in particular to a molybdenum alloy and its preparation method. Background Technology
[0002] Molybdenum is a refractory metal with a melting point of 2610℃. Below this melting point, its crystal structure remains stable without undergoing a phase transition. Due to its excellent electrical and thermal conductivity, thermal stability, and high-temperature strength, molybdenum and its derivative alloys are widely used in electronic components, semiconductors, missiles, and as candidate materials for nuclear fusion reactor components.
[0003] However, due to the inherent brittleness of molybdenum alloys, their ductility at room temperature is poor, and insufficient intergranular bonding makes the materials difficult to process. Furthermore, molybdenum and its alloys have poor weldability, making it difficult to meet the growing demand for superior comprehensive performance of molybdenum materials in civilian and defense fields. The low ductility of molybdenum and its alloys can be attributed to two reasons: molybdenum is difficult to activate dislocations at room temperature, especially below the brittle transition temperature; and interstitial elements oxygen and nitrogen tend to segregate to grain boundaries, thereby weakening their strength and leading to brittle fracture. Currently, improving the room temperature ductility and weldability of molybdenum alloys is the main research objective in the field of molybdenum and related alloy materials.
[0004] Based on an in-depth analysis of the application bottlenecks of traditional commercially available ODS molybdenum alloys (such as molybdenum-lanthanum and molybdenum-zirconium alloys), significant shortcomings exist in high-temperature oxidation resistance, room-temperature toughness, high purity, machinability, weldability, and product quality consistency, severely limiting their reliability and application scope in cutting-edge fields such as electronics, semiconductors, and nuclear energy. It is difficult for ODS molybdenum alloys produced using traditional processes to simultaneously address all of these issues.
[0005] In summary, there is an urgent need to innovate molybdenum alloys in order to achieve a good balance between strength and ductility. Summary of the Invention
[0006] In view of this, the present invention provides a molybdenum alloy and a method for preparing the same, the main purpose of which is to improve the strength and plasticity of the molybdenum alloy.
[0007] To achieve the above objectives, the present invention mainly provides the following technical solutions:
[0008] On one hand, embodiments of the present invention provide a molybdenum alloy, wherein, by mass percentage, the molybdenum alloy comprises the following chemical components:
[0009] Rare earth element Y: 0.20wt%-0.30wt%;
[0010] Zr: 0.12wt%-0.20wt%;
[0011] W: 0.20wt%-0.30wt%;
[0012] The balance is Mo and unavoidable impurities;
[0013] The microstructure of the molybdenum alloy comprises a molybdenum matrix and nano-reinforcing phases dispersed within the molybdenum matrix; wherein the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y₂O₃. x Zr y O (1.5x+2y) A composite oxide, wherein the nano-reinforcing phase and the molybdenum matrix have a coherent or semi-coherent interface structure; wherein x takes the value of 0.1-5 and y takes the value of 0.1-5.
[0014] Preferably, the strengthening methods of the molybdenum alloy include nanophase dispersion strengthening and solid solution strengthening of tungsten.
[0015] Preferably, the nano-reinforced phase has a spherical morphology and a particle size of 10nm-150nm.
[0016] Preferably, the molybdenum alloy has a tensile strength greater than or equal to 570 MPa and an elongation at break greater than 22% at room temperature.
[0017] On the other hand, embodiments of the present invention also provide a method for preparing the molybdenum alloy according to any one of the above claims, wherein the method for preparing the molybdenum alloy includes the following steps:
[0018] Step 1): After mixing ammonium molybdate, ammonium tungstate, rare earth yttrium salt, zirconium salt and water, heat and stir to promote the dissolution of ammonium molybdate, ammonium tungstate, rare earth yttrium salt and zirconium salt to obtain a precursor solution;
[0019] Step 2): The precursor solution is heated to precipitate the complex precursor, and then dried to obtain a mixed powder;
[0020] Step 3): The mixed powder is calcined to obtain doped molybdenum oxide powder;
[0021] Step 4): The doped molybdenum oxide powder is reduced under a reducing atmosphere to obtain molybdenum powder;
[0022] Step 5): The molybdenum powder is sintered to obtain the molybdenum alloy.
[0023] Preferably, in step 1): the ammonium molybdate is any one or more of ammonium dimolybdate, ammonium tetramolybdate, and ammonium heptamolybdate; the ammonium tungstate is ammonium paratungstate and / or ammonium metatungstate; the rare earth yttrium salt is yttrium nitrate and / or yttrium acetate; and the zirconium salt is nitrate and / or acetate.
[0024] Preferably, in step 2): after filtering the precursor solution to remove impurities, citric acid is added dropwise to adjust the pH value to 1-3 to clarify the liquid, and then the liquid is heated to precipitate the complex precursor; after drying the complex precursor, the mixed powder is obtained.
[0025] Preferably, in step 2), the temperature of the heat treatment is 65℃-85℃, and the heat treatment time is 10min-30min.
[0026] Preferably, in step 2), the drying process is either spray drying or freeze drying.
[0027] Preferably, in step 3), the calcination temperature is 450℃-600℃, the calcination atmosphere is air or oxygen, and the calcination time is 1h-3h.
[0028] Preferably, in step 4), the doped molybdenum oxide powder is heated to 520℃-680℃ and held for 1h-3h in a hydrogen reducing atmosphere, and then heated to 700℃-850℃ and held for 2h-6h to perform a reduction treatment to obtain molybdenum powder; wherein the particle size of the molybdenum powder is 300nm-2000nm.
[0029] Preferably, in step 4), during the reduction process: the reduction process is carried out in a hydrogen furnace, wherein the thickness of the doped molybdenum oxide powder in the reduction boat is 3mm-5mm.
[0030] Preferably, in step 4), during the reduction process, molybdenum powder is continuously deposited on the surface using nano-oxide particles as nucleation sites, resulting in a core-shell structure of molybdenum powder with oxide particles as the core and molybdenum powder as the shell; wherein the oxides include rare earth oxides and zirconium oxide; and W element is dissolved in molybdenum powder.
[0031] Preferably, in step 5): the molybdenum powder is heated to 1000℃-1100℃ and sintered for 0.5h-1.5h, then heated to 1150℃-1350℃ and sintered for 1h-3h, then heated to 1400℃-1600℃ and sintered for 2h-5h, and finally heated to 2050℃-2150℃ and sintered for 4h-8h to obtain the molybdenum alloy; wherein the sintering pressure is 20MPa-50MPa.
[0032] Compared with the prior art, the molybdenum alloy and its preparation method of the present invention have at least the following beneficial effects:
[0033] On one hand, embodiments of the present invention provide a molybdenum alloy, wherein, by mass percentage, the molybdenum alloy comprises the following chemical composition: rare earth Y: 0.20wt%-0.30wt%, Zr: 0.12wt%-0.20wt%, W: 0.20wt%-0.30wt%, with the balance being Mo and unavoidable impurities. Here, embodiments of the present invention, through the above-mentioned composition design, regulate the size and distribution of the second phase, introduce coherent / semi-coherent rare earth composite oxides that form with the matrix, simultaneously achieving grain refinement and grain boundary purification, and successfully preparing a high-performance molybdenum alloy with composite strengthening effect (excellent strength and plasticity).
[0034] Specifically, the molybdenum alloy provided in this embodiment of the invention, through the above-mentioned composition design and corresponding preparation process, yields the following microstructure: the microstructure of the molybdenum alloy includes a molybdenum matrix and nano-reinforcing phases dispersed in the molybdenum matrix; wherein, the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y x Zr y O (1.5x+2y) The composite oxide, wherein the nano-reinforcing phase forms a coherent or semi-coherent interface structure with the molybdenum matrix. Specifically, in the microstructure of the molybdenum alloy, these nanoparticles (Y₂O₃, ZrO₂, and Y₂O₃) form a composite oxide. x Zr y O (1.5x+2y) In particular, the Y-Zr-O composite phase can form a coherent or semi-coherent interface with the molybdenum matrix. This interface has low energy and strong bonding, effectively pinning dislocations and grain boundaries to produce a strong dispersion strengthening effect. It also inhibits grain growth and refines the grains during sintering. Simultaneously, rare earth elements have a strong adsorption and fixation effect on interstitial atoms (especially oxygen), purifying grain boundaries and significantly improving grain boundary bonding strength. Further details are provided below: Grain boundary brittleness is a major reason for the low strength and ductility of molybdenum alloys. For example, under stress, molybdenum alloys fail prematurely due to low grain boundary strength, resulting in very low mechanical properties and strength / ductility. However, the nanophase in the molybdenum alloy of this invention forms a coherent or semi-coherent interface with the matrix. This low interface energy and strong bonding not only effectively pins dislocations and grain boundaries to produce a strong dispersion strengthening effect but also inhibits grain growth and refines the grains during sintering. Therefore, based on dispersion strength, grain refinement strengthening, and dislocation pile-up theory, the strength of the molybdenum alloy is improved. The improved plasticity is due to the strong adsorption and fixation effect of rare earth elements on interstitial atoms (especially oxygen), which purifies grain boundaries. High oxygen content at grain boundaries leads to embrittlement and lower bonding strength, thus shortening the plastic deformation process. Purifying grain boundaries significantly improves grain boundary bonding strength. The improvement in strength and plasticity is a combined result. Furthermore, compared to forged samples, the molybdenum alloy of this invention is in a sintered state without deformation texture, which helps improve weldability.
[0035] On the other hand, embodiments of the present invention provide a method for preparing the above-mentioned molybdenum alloy, comprising the following steps: Step 1): Ammonium molybdate, ammonium tungstate, rare earth yttrium salt, zirconium salt and water are mixed and heated and stirred to promote the dissolution of ammonium molybdate, ammonium tungstate, rare earth yttrium salt and zirconium salt, to obtain a precursor solution; Step 2): The precursor solution is heated to precipitate a complex precursor, and then dried to obtain a mixed powder; Step 3): The mixed powder is calcined to obtain doped molybdenum oxide powder; Step 4): The doped molybdenum oxide powder is reduced under a reducing atmosphere to obtain molybdenum powder; Step 5): The molybdenum powder is sintered to obtain the molybdenum alloy. Here, the above steps should be explained as follows: The present invention uses ammonium molybdate, ammonium tungstate and rare earth salt as raw materials, and while reducing production costs, obtains ultrafine molybdenum powder with low oxygen content, high dispersion and high porosity through multi-temperature reduction treatment. During the reduction process, molybdenum powder continuously deposits on the surface using nano-rare earth oxide particles as nucleation sites, forming a core-shell structure of rare earth oxide particles and ultrafine molybdenum powder. This ensures that the reinforcing phase is uniformly distributed within the grains during sintering. The above-mentioned solution of this invention simplifies the process flow, eliminating the need for forging to obtain a high-strength, high-ductility molybdenum alloy with a room temperature strength exceeding 570 MPa and an elongation exceeding 22%, significantly reducing production costs and energy consumption, and conforming to green manufacturing principles. The use of rare earth acetate effectively reduces the emission of harmful gases, greatly lowering the environmental protection costs of enterprises during production.
[0036] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Attached Figure Description
[0037] Figure 1 This is a microstructure diagram of the molybdenum alloy prepared in Example 1;
[0038] Figure 2 The image shows the microstructure of the molybdenum alloy prepared in Comparative Example 1.
[0039] Figure 3 The image shows the microstructure of the molybdenum alloy prepared in Comparative Example 2.
[0040] Figure 4 The image shows the microstructure of the molybdenum alloy prepared in Comparative Example 3.
[0041] Figure 5 The image shows the microstructure of the molybdenum alloy prepared in Comparative Example 4.
[0042] Figure 6 The image shows the microstructure of the molybdenum alloy prepared in Comparative Example 5.
[0043] Figure 7These are the tensile property curves of the molybdenum alloys prepared in the examples and comparative examples. Detailed Implementation
[0044] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects according to the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.
[0045] This invention aims to systematically overcome these bottlenecks through compositional innovation and process optimization, thereby enhancing my country's independent innovation capabilities in the field of high-performance refractory metal materials. By optimizing compositional design, this invention creates a novel ODS molybdenum alloy that combines dispersion strengthening and solid solution strengthening effects. By controlling the size and distribution of the second phase and introducing coherent / semi-coherent rare-earth composite oxides to form with the matrix, the invention simultaneously refines grains and purifies grain boundaries, achieving a good match between room-temperature strength and ductility in the molybdenum alloy and improving its weldability, making it highly valuable for engineering applications.
[0046] The main solution of the present invention is as follows:
[0047] On one hand, embodiments of the present invention provide a molybdenum alloy, wherein, by mass percentage, the molybdenum alloy comprises the following chemical components:
[0048] Rare earth elements Y: 0.20wt%-0.30wt%; Zr: 0.12wt%-0.20wt%; W: 0.20wt%-0.30wt%; balance is Mo and unavoidable impurities.
[0049] The strengthening methods of the molybdenum alloy include nanophase dispersion strengthening and solid solution strengthening of tungsten.
[0050] The microstructure of the molybdenum alloy comprises a molybdenum matrix and nano-reinforcing phases dispersed within the molybdenum matrix; wherein the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y₂O₃. x Zr y O (1.5x+2y) A composite oxide, wherein the nano-reinforcing phase and the molybdenum matrix have a coherent or semi-coherent interface structure; wherein x takes the value of 0.1-5 and y takes the value of 0.1-5.
[0051] The nano-reinforced phase has a spherical morphology and a particle size of 10nm-150nm.
[0052] The molybdenum alloy has a tensile strength of ≥570 MPa and an elongation at break of ≥22% at room temperature.
[0053] It should be noted that the nanoparticles dispersed in the molybdenum matrix mentioned above include Y₂O₃, ZrO₂, and Y₂O₃. x Zr y O (1.5x+2y) Composite oxides, especially the Y-Zr-O composite phase as the core functional phase, form coherent or semi-coherent interfaces with the molybdenum matrix, possessing inherent characteristics of low interfacial energy and high interfacial bonding strength. This interfacial structure effectively pins dislocation movement and grain boundary slip during alloy deformation under load, generating a significant dispersion strengthening effect. Furthermore, during alloy sintering, it inhibits abnormal grain growth in the molybdenum matrix, achieving uniform grain refinement and further solidifying the alloy's mechanical strength through a grain refinement strengthening mechanism.
[0054] To address the common technical deficiency in existing molybdenum alloys—the difficulty in simultaneously achieving grain boundary brittleness and high plasticity—this invention achieves simultaneous purification and strengthening of grain boundaries through the precise addition of rare earth elements. Rare earth elements exhibit strong selective adsorption and fixation of interstitial atoms, especially oxygen atoms that tend to agglomerate at grain boundaries. This effectively eliminates the enrichment of interstitial oxygen at grain boundaries, fundamentally alleviating the grain boundary embrittlement problem caused by oxygen, significantly improving grain boundary bonding strength, preventing early intergranular cracking during plastic deformation, and greatly expanding the alloy's plastic deformation capacity. This solves the industry pain point of traditional molybdenum alloys where increased strength is accompanied by decreased plasticity.
[0055] Meanwhile, by introducing solid-solution W elements into the molybdenum alloy of the present invention, the matrix lattice distortion can be induced by the lattice mismatch between W atoms and Mo atoms, resulting in a significant solid-solution strengthening effect. This, together with the aforementioned dispersion strengthening and grain refinement strengthening mechanisms, forms a multi-dimensional synergistic effect, further improving the strength performance of the alloy and ultimately achieving simultaneous optimization of the alloy's strength and plasticity.
[0056] On the other hand, embodiments of the present invention provide a method for preparing the above-mentioned molybdenum alloy, wherein the method for preparing the molybdenum alloy includes the following steps:
[0057] Step 1): Mix ammonium molybdate, ammonium tungstate, rare earth yttrium salt, zirconium salt and water, then heat and stir to promote the dissolution of ammonium molybdate, ammonium tungstate, rare earth yttrium salt and zirconium salt to obtain a precursor solution.
[0058] Wherein, the ammonium molybdate is any one or more of ammonium dimolybdate, ammonium tetramolybdate, and ammonium heptamolybdate.
[0059] Among them, ammonium tungstate is ammonium paratungstate and / or ammonium metatungstate.
[0060] The rare earth yttrium salt is a yttrium nitrate salt and / or a yttrium acetate salt. The zirconium salt is a nitrate salt and / or an acetate salt.
[0061] It should be noted that ammonium molybdate, ammonium tungstate, rare earth yttrium salts, and zirconium salts can be in anhydrous or hydrated form.
[0062] The water used is deionized water. The amount of water used is determined to ensure that the raw materials dissolve in the water.
[0063] Preferably, the heating method is constant temperature water bath heating at 65°C. The heating time is determined by the amount of solute dissolved.
[0064] Preferably, magnetic stirring is used for the stirring process, wherein the rotation speed is greater than 80 revolutions per minute and the duration is greater than 30 minutes.
[0065] In this step, the amounts of ammonium molybdate, ammonium tungstate, rare earth yttrium salt, and zirconium salt are determined by calculation to ensure that the chemical composition of the final molybdenum alloy meets the following requirements: rare earth Y: 0.20wt%-0.30wt%, Zr: 0.12wt%-0.20wt%, W: 0.20wt%-0.30wt%, with the balance being Mo and unavoidable impurities.
[0066] Step 2): The precursor solution is heated to precipitate the complex precursor, and then dried to obtain a mixed powder.
[0067] Preferably, this step specifically involves: filtering the precursor solution to remove impurities, adding citric acid to adjust the pH of the liquid to 1-3 to make the solution clear, heating to form a complex precursor (gel state), and drying to obtain a mixed powder.
[0068] The heating method is constant temperature water bath heating at 65-85℃, and the heating time is 10-30 minutes.
[0069] The drying method is vacuum drying, spray drying, or freeze drying.
[0070] The mixed powder is a mixture of rare earth molybdenum salts.
[0071] This step mainly involves complexing the raw materials and removing moisture.
[0072] Step 3): The mixed powder is calcined to obtain doped molybdenum oxide powder (doping here refers to the incorporation of rare earth, Zr, and W elements).
[0073] Preferably, in this step, the roasting process is carried out in a muffle furnace.
[0074] Preferably, the calcination temperature is 450℃-600℃, the calcination atmosphere is air or oxygen, and the calcination time is 1h-3h.
[0075] This step primarily involves oxidizing the various components in the mixed powder. For example, molybdenum forms molybdenum oxide, and rare earth elements also form oxides.
[0076] Step 4): Under a reducing atmosphere, the doped molybdenum oxide powder is subjected to a reduction treatment to reduce the molybdenum oxide to molybdenum, thereby obtaining molybdenum powder.
[0077] Preferably, under a hydrogen reducing atmosphere, the doped molybdenum oxide powder is heated to 520℃-680℃ and held for 1h-3h, preferably 2h, and then heated to 700℃-850℃ and held for 2h-6h to carry out reduction treatment to obtain molybdenum powder.
[0078] In the reduction process, the thickness of the doped molybdenum oxide powder is 3mm-5mm, resulting in ultrafine molybdenum powder with low oxygen content, high dispersion, and high porosity; the particle size of the ultrafine molybdenum powder is 300nm-2000nm.
[0079] During the reduction process, molybdenum powder is continuously deposited on the surface of nano-oxide particles as nucleation sites, resulting in a core-shell structure of molybdenum powder with oxide particles as the core and molybdenum powder as the shell; wherein the oxides include rare earth oxides and zirconium oxide; W element is dissolved in molybdenum powder.
[0080] Step 5): The molybdenum powder is sintered to obtain the molybdenum alloy.
[0081] Preferably, the molybdenum powder is heated to 1000℃-1100℃ and sintered for 0.5h-1.5h, then heated to 1150℃-1350℃ and sintered for 1h-3h, then heated to 1400℃-1600℃ and sintered for 2h-5h, and finally heated to 2050℃-2150℃ and sintered for 4h-8h to obtain the molybdenum alloy; wherein the sintering pressure is 20MPa-50MPa.
[0082] The following examples and comparative examples further illustrate this point:
[0083] Example 1
[0084] This embodiment provides a method for preparing a molybdenum alloy, including the following steps:
[0085] Step 1): Weigh 14.2g of anhydrous yttrium tetraacetate, 8g of anhydrous zirconium acetate, 3.6g of anhydrous ammonium tungstate, and 1820g of anhydrous ammonium molybdate into deionized water (add deionized water continuously until the solutes are completely dissolved). Heat and stir to promote the dissolution of the raw materials, obtaining a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is done with a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0086] Step 2): After filtering impurities from the precursor solution, citric acid is added to adjust the pH of the solution to 1. The solution is heated in a water bath to 80°C to precipitate the complex precursor. The complex precursor is then sprayed and dried to obtain a dry mixed powder.
[0087] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0088] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and heated in a hydrogen furnace to 550°C for 2 hours, then heated to 800°C for 4 hours to carry out reduction treatment, so as to obtain molybdenum alloy powder with low oxygen content, high dispersion, high porosity and particle size of 300nm-2000nm.
[0089] The thickness of the material in the molybdenum oxide powder reduction boat is 3mm;
[0090] Step 5): Heat the molybdenum alloy powder to 1000℃ and sinter for 1 hour, then raise the temperature to 1200℃ and sinter for 2 hours, then raise the temperature to 1400℃ and sinter for 2 hours, and finally raise the temperature to 2100℃ and sinter for 5 hours. The sintering pressure is 40 MPa, and a high-performance sintered molybdenum alloy is obtained.
[0091] See Figure 7 As shown, the molybdenum alloy prepared in this embodiment has a tensile strength of over 570 MPa and an elongation at break of over 25%.
[0092] The chemical composition of the molybdenum alloy prepared in this embodiment, by mass fraction, is as follows: Y: 0.28wt%, Zr: 0.14wt%, W: 0.24wt%, with the balance being molybdenum.
[0093] like Figure 1 As shown, the microstructure of the molybdenum alloy prepared in this embodiment is as follows: the microstructure of the molybdenum alloy includes a molybdenum matrix and nano-reinforcing phases dispersed in the molybdenum matrix; wherein, the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y x Zr y O (1.5x+2y) A composite oxide, wherein the nano-reinforcing phase and the molybdenum matrix have a coherent or semi-coherent interface structure; wherein x takes the value of 0.1-5 and y takes the value of 0.1-5.
[0094] Example 2
[0095] This embodiment provides a method for preparing a molybdenum alloy, including the following steps:
[0096] Step 1): Weigh 15.2g of anhydrous yttrium nitrate, 8.6g of anhydrous zirconium nitrate, 3.6g of anhydrous ammonium tungstate, and 1820g of anhydrous ammonium molybdate into deionized water and heat and stir to promote the dissolution of the raw materials, obtaining a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is performed using a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0097] Step 2): After filtering impurities from the precursor solution, citric acid is added to the precursor solution to adjust the pH value to 1. The solution is heated to 80°C in a water bath to obtain the complex precursor. The complex precursor is then sprayed and dried to obtain a dry mixed powder.
[0098] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0099] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and heated to 550°C in a hydrogen furnace for 2 hours, then heated to 800°C and held for 4 hours for reduction treatment to obtain molybdenum alloy powder with low oxygen content, high dispersion, and high porosity particle size.
[0100] The thickness of the molybdenum oxide powder in the reduction boat is 3 mm.
[0101] Step 5): Heat the molybdenum alloy powder to 1100℃ and sinter for 1 hour, then raise the temperature to 1250℃ and sinter for 2 hours, then raise the temperature to 1500℃ and sinter for 3 hours, and finally raise the temperature to 2100℃ and sinter for 6 hours. The sintering pressure is 40 MPa, and a high-performance sintered molybdenum alloy is obtained.
[0102] See Figure 7 As shown, the molybdenum alloy prepared in this embodiment has a tensile strength of over 570 MPa and an elongation at break of over 22%.
[0103] The chemical composition of the molybdenum alloy prepared in this embodiment, by mass fraction, is as follows: Y: 0.21%, Zr: 0.19%, W: 0.24%, with the balance being molybdenum.
[0104] The microstructure of the molybdenum alloy prepared in this embodiment is as follows: the microstructure of the molybdenum alloy includes a molybdenum matrix and nano-reinforcing phases dispersed in the molybdenum matrix; wherein, the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y x Zr y O (1.5x+2y) A composite oxide, wherein the nano-reinforcing phase and the molybdenum matrix have a coherent or semi-coherent interface structure; wherein x takes the value of 0.1-5 and y takes the value of 0.1-5.
[0105] Comparative Example 1
[0106] Comparative Example 1 prepared a molybdenum alloy, mainly including the following steps:
[0107] Step 1): Weigh 6 grams of Y2O3, 3 grams of ZrO2, and 988.5 grams of commercial molybdenum powder and add them to a ball mill. Ball milling is carried out in an Ar atmosphere to obtain doped molybdenum powder.
[0108] The ball mill operates at a speed of 220 r / min and a milling time of 8 h.
[0109] Step 2): The doped molybdenum powder obtained in Step 1 is heated to 1000℃ and sintered for 1 hour, then heated to 1200℃ and sintered for 2 hours, then heated to 1400℃ and sintered for 2 hours, and finally heated to 2100℃ and sintered for 5 hours. The sintering pressure is 40 MPa to obtain a molybdenum alloy.
[0110] Among them, see Figure 7 As shown, the room temperature tensile strength of the molybdenum alloy obtained in Comparative Example 1 is about 470 MPa, and the room temperature elongation at break is about 6%.
[0111] The chemical composition of the molybdenum alloy prepared in Comparative Example 1 is as follows: Y: 0.37%, Zr: 0.20wt%, with the balance being Mo.
[0112] The microstructure of the molybdenum alloy prepared in Comparative Example 1 is shown in [reference]. Figure 2 As shown in the figure, the molybdenum alloy prepared in Comparative Example 1 has poor overall performance. The core reasons include four points: First, the molybdenum alloy does not contain W, and therefore completely lacks the performance contribution of solid solution strengthening; Second, the second phase of the molybdenum alloy is large in size and has poor interfacial bonding with the matrix, which greatly weakens the effects of fine grain strengthening and dispersion strengthening; Third, the large second phase is prone to agglomeration at grain boundaries, becoming the source of crack initiation and propagation, further deteriorating the alloy performance; Fourth, the alloy grain size is relatively large and the degree of recrystallization is high, which exacerbates the segregation of elements at grain boundaries and significantly weakens the grain boundary performance.
[0113] Comparative Example 2
[0114] Comparative Example 2 provides a method for preparing a molybdenum alloy, comprising the following steps:
[0115] Step 1): Weigh 7.1g of yttrium tetraacetate, 8g of zirconium acetate, 3.6g of ammonium tungstate, and 1820g of ammonium molybdate into deionized water and heat and stir to promote the dissolution of the raw materials, obtaining a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is done using a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0116] Step 2): After filtering impurities from the precursor solution, add citric acid to adjust the pH of the solution to 1, heat in a water bath to 80°C to precipitate the complex precursor in the solution, and spray-dry the complex precursor to obtain a dry mixed powder.
[0117] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0118] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and placed in a hydrogen furnace to be heated to 550°C and held for 2 hours. Then, the temperature is raised to 800°C and held for 4 hours to carry out the reduction treatment and obtain mixed molybdenum powder.
[0119] The thickness of the molybdenum oxide powder in the reduction boat is 3 mm.
[0120] Step 5): Heat the mixed molybdenum powder to 1000℃ and sinter for 1 hour, then raise the temperature to 1200℃ and sinter for 2 hours, then raise the temperature to 1400℃ and sinter for 2 hours, and finally raise the temperature to 2100℃ and sinter for 5 hours. The sintering pressure is 40 MPa to obtain a sintered molybdenum alloy.
[0121] See Figure 7 As shown, the molybdenum alloy prepared in Comparative Example 2 has a tensile strength of over 420 MPa and an elongation at break of over 4%.
[0122] The chemical composition of the molybdenum alloy prepared in Comparative Example 2 is as follows: Y: 0.031 wt%, Zr: 0.043 wt%, W: 0.32 wt%, with the balance being Mo.
[0123] The microstructure of the molybdenum alloy prepared in Comparative Example 2 is shown in [reference]. Figure 3 As shown in the figure. In Comparative Example 2, due to insufficient addition of Y element, the volume fraction of the second phase particles generated in situ during the alloy sintering process was low, failing to form a uniformly dispersed pinning system in the molybdenum matrix, resulting in significantly insufficient dispersion strengthening effect. Simultaneously, the low volume fraction of the second phase could not effectively pin and impede the grain boundaries of the molybdenum matrix, leading to significant abnormal grain growth during high-temperature sintering, completely negating the grain refinement strengthening effect achieved by the nano-second phase described in this invention. The dual deficiency of these two core mechanisms—dispersion strengthening and grain refinement strengthening—ultimately resulted in the molybdenum alloy prepared in the comparative example having significantly inferior overall mechanical properties compared to the embodiments of this invention.
[0124] Comparative Example 3
[0125] Comparative Example 3 provides a method for preparing a molybdenum alloy, comprising the following steps:
[0126] Step 1): Weigh 21.3g of yttrium tetraacetate, 8g of zirconium acetate, 3.6g of ammonium tungstate, and 1820g of ammonium molybdate into deionized water and heat and stir to promote the dissolution of the raw materials, obtaining a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is done with a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0127] Step 2): After filtering impurities from the precursor solution, add citric acid to adjust the pH of the solution to 1, heat in a water bath to 80°C to precipitate the complex precursor in the solution, and spray-dry the complex precursor to obtain a dry mixed powder.
[0128] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0129] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and placed in a hydrogen furnace to be heated to 550°C and held for 2 hours. Then, the temperature is raised to 800°C and held for 4 hours to carry out the reduction treatment and obtain mixed molybdenum powder.
[0130] The thickness of the molybdenum oxide powder in the reduction boat is 3 mm.
[0131] Step 5): Heat the mixed molybdenum powder to 1000℃ and sinter for 1 hour, then raise the temperature to 1200℃ and sinter for 2 hours, then raise the temperature to 1400℃ and sinter for 2 hours, and finally raise the temperature to 2100℃ and sinter for 5 hours. The sintering pressure is 40 MPa to obtain a sintered molybdenum alloy.
[0132] See Figure 7 As shown, the molybdenum alloy prepared in this embodiment has a tensile strength of over 500 MPa and an elongation at break of over 1%.
[0133] The chemical composition of the molybdenum alloy prepared in Comparative Example 3 is as follows: Y: 0.60 wt%, Zr: 0.19 wt%, W: 0.29 wt%, with the balance being Mo.
[0134] The microstructure of the molybdenum alloy prepared in Comparative Example 3 is as follows: Figure 4 As shown. The amount of Y element added in Comparative Example 3 is relatively high. Due to the higher amount of rare earth elements added, Comparative Example 3 shows that rare earth oxides and Y are generated in situ in the alloy. x Zr y O (1.5x+2y)The volume fraction of the rare-earth-zirconium composite oxide exceeds the optimal range for achieving a uniform and dispersed distribution. The nucleation and growth of the second-phase particles cannot be effectively controlled, leading to agglomeration and abnormal coarsening at the grain boundaries of the molybdenum matrix. These agglomerated and coarsened second-phase particles induce severe stress concentration during alloy deformation under load, disrupting the integrity of the grain boundary structure and significantly reducing grain boundary bonding strength. This completely fails to achieve the nano-strengthening effect of dislocation pinning and structural stabilization at grain boundaries as described in this application. Furthermore, the grain refinement effect of this comparative example is essentially the same as in Example 2, failing to achieve additional performance improvements through the grain refinement strengthening mechanism or synergistic effects with other strengthening mechanisms. Ultimately, the strength and plasticity of the molybdenum alloy prepared in Comparative Example 3 are significantly lower than those in the embodiments of this invention.
[0135] Comparative Example 4
[0136] Comparative Example 4 provides a method for preparing a molybdenum alloy, comprising the following steps:
[0137] Step 1): Weigh 28.4g of yttrium tetraacetate, 8g of zirconium acetate, 3.6g of ammonium tungstate, and 1820g of ammonium molybdate into deionized water and heat and stir to promote the dissolution of the raw materials, obtaining a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is done using a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0138] Step 2): Add citric acid to the precursor solution to adjust the pH value to 1, heat in a water bath to 80°C to obtain the complex precursor in the solution, spray dry the complex precursor to obtain a dry mixed powder.
[0139] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0140] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and placed in a hydrogen furnace and heated to 550°C for 2 hours, then heated to 800°C for 4 hours, and finally heated to 900°C for 4 hours for reduction treatment to obtain mixed molybdenum powder.
[0141] The thickness of the molybdenum oxide powder in the reduction boat is 3 mm.
[0142] Step 5): Heat the mixed molybdenum powder to 1000℃ and sinter for 1 hour, then raise the temperature to 1200℃ and sinter for 2 hours, then raise the temperature to 1400℃ and sinter for 2 hours, and finally raise the temperature to 2100℃ and sinter for 5 hours. The sintering pressure is 40 MPa to obtain a sintered molybdenum alloy.
[0143] See Figure 7As shown, the molybdenum alloy prepared in Comparative Example 4 has a tensile strength of over 490 MPa and an elongation at break of over 1%.
[0144] The chemical composition of the molybdenum alloy prepared in Comparative Example 4 is as follows: Y: 0.83 wt%, Zr: 0.17 wt%, W: 0.29 wt%, with the balance being Mo.
[0145] The microstructure of the molybdenum alloy prepared in Comparative Example 4 is as follows: Figure 5 As shown. Compared with Examples and Comparative Example 3, Comparative Example 4 has a higher rare earth content, resulting in a higher volume fraction of rare earth oxides or mixed oxides of rare earth and zirconium elements. The oxide particles grow further and are more likely to agglomerate and grow at the grain boundaries, which easily leads to stress concentration and further reduces the grain boundary strength. The grain refinement effect is similar to that of Examples, so the strength and plasticity are weaker than those of Examples. Compared with Comparative Example 3, the performance of the molybdenum alloy in Comparative Example 4 is further deteriorated.
[0146] Comparative Example 5
[0147] Comparative Example 5 provides a method for preparing a molybdenum alloy, comprising the following steps:
[0148] Step 1): Weigh 1820g of ammonium molybdate and place it in deionized water. Heat and stir the solution to promote dissolution and obtain a precursor solution (a uniformly mixed, clear solution). Heating is performed using a water bath at 65℃, and stirring is done with a magnetic stirrer at 120 rpm. The heating and stirring process lasts for 120 minutes.
[0149] Step 2): Add citric acid to the precursor solution to adjust the pH value to 1, heat in a water bath to 80°C to obtain the complex precursor in the solution, spray dry the complex precursor to obtain dry powder.
[0150] Step 3): In a muffle furnace, the mixed powder is calcined at 450°C for 2 hours to obtain doped molybdenum oxide powder.
[0151] Step 4): The doped molybdenum oxide powder is loaded into a reduction boat and placed in a hydrogen furnace and heated to 550°C for 2 hours. Then, the temperature is increased to 800°C and held for 4 hours. Finally, the temperature is increased to 900°C and held for 4 hours to carry out reduction treatment, so as to obtain molybdenum powder with low oxygen content, high dispersion, and high porosity.
[0152] The thickness of the molybdenum oxide powder in the reduction boat is 3 mm.
[0153] Step 5): Heat the molybdenum powder to 1000℃ and sinter for 1 hour, then raise the temperature to 1200℃ and sinter for 2 hours, then raise the temperature to 1400℃ and sinter for 2 hours, and finally raise the temperature to 2100℃ and sinter for 5 hours. The sintering pressure is 40 MPa to obtain a sintered molybdenum alloy.
[0154] See Figure 7 As shown, the molybdenum alloy prepared in Comparative Example 5 has a tensile strength of over 440 MPa and an elongation at break of over 4%.
[0155] The chemical composition of the molybdenum alloy prepared in Comparative Example 5 is as follows: Y: 0 wt%, Zr: 0 wt%, W: 0 wt%, with the balance being Mo.
[0156] The microstructure of the molybdenum alloy prepared in Comparative Example 5 is as follows: Figure 6 As shown, Comparative Example 5 did not add any reinforcing phase-related elements; this comparative example could neither generate a dispersed nano-reinforcing phase in situ within the molybdenum matrix, nor achieve a completely nucleated dispersed strengthening effect, nor did it have corresponding alloying elements to achieve matrix solid solution, thus failing to obtain the performance gain from solid solution strengthening. Due to the lack of effective pinning effect of the nano-second phase on grain boundaries, the molybdenum matrix grains underwent significant abnormal growth during alloy sintering, with grain sizes much larger than those in the embodiments of this application; the complete absence of the core strengthening mechanism, coupled with the dual effects of grain coarsening, ultimately resulted in the molybdenum alloy prepared in Comparative Example 5 having significantly inferior strength and plasticity compared to the corresponding embodiments of this application.
[0157] In summary, this invention utilizes the synergistic effect of nano-dispersion strengthening and solid solution strengthening, as well as the pinning and purification effect of rare earth oxides on grain boundaries, to prepare a molybdenum alloy that possesses both high strength (tensile strength at room temperature ≥570MPa) and high plasticity (elongation at break ≥25%). Furthermore, the process is simple and environmentally friendly, making it suitable for high-end fields with stringent requirements for strength and toughness.
[0158] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A molybdenum alloy, characterized in that, The molybdenum alloy comprises the following chemical components by weight percentage: Rare earth element Y: 0.20wt%-0.30wt%; Zr: 0.12wt%-0.20wt%; W: 0.20wt%-0.30wt%; The balance is Mo and unavoidable impurities; The microstructure of the molybdenum alloy comprises a molybdenum matrix and nano-reinforcing phases dispersed within the molybdenum matrix; wherein the nano-reinforcing phases include Y₂O₃, ZrO₂, and Y₂O₃. x Zr y O (1.5x+2y) A composite oxide, wherein the nano-reinforcing phase and the molybdenum matrix have a coherent or semi-coherent interface structure; wherein x takes the value of 0.1-5 and y takes the value of 0.1-5; The preparation method of the molybdenum alloy includes the following steps: Step 1): After mixing ammonium molybdate, ammonium tungstate, rare earth yttrium salt, zirconium salt and water, heat and stir to promote the dissolution of ammonium molybdate, ammonium tungstate, rare earth yttrium salt and zirconium salt to obtain a precursor solution; Step 2): The precursor solution is heated to precipitate the complex precursor, and then dried to obtain a mixed powder; Step 3): The mixed powder is calcined to obtain doped molybdenum oxide powder; Step 4): The doped molybdenum oxide powder is reduced under a reducing atmosphere to obtain molybdenum powder; Step 5): The molybdenum powder is sintered to obtain the molybdenum alloy; In step 4): Under a hydrogen reducing atmosphere, the doped molybdenum oxide powder is heated to 520℃-680℃ and held for 1h-3h, and then heated to 700℃-850℃ and held for 2h-6h to carry out reduction treatment to obtain molybdenum powder; wherein the particle size of the molybdenum powder is 300nm-2000nm. During the reduction process: The reduction process is carried out in a hydrogen furnace, wherein the thickness of the doped molybdenum oxide powder in the reduction boat is 3mm-5mm. During the reduction process, molybdenum powder is continuously deposited on the surface using nano-oxide particles as nucleation sites, resulting in a core-shell structure of molybdenum powder with oxide particles as the core and molybdenum powder as the shell; wherein, the oxides include rare earth oxides and zirconium oxide; W element is dissolved in molybdenum powder.
2. The molybdenum alloy according to claim 1, characterized in that, The strengthening methods of the molybdenum alloy include nanophase dispersion strengthening and tungsten solid solution strengthening.
3. The molybdenum alloy according to claim 1, characterized in that, The nano-reinforced phase has a spherical morphology with a particle size of 10nm-150nm.
4. The molybdenum alloy according to claim 1, characterized in that, The molybdenum alloy has a tensile strength greater than or equal to 570 MPa and an elongation at break greater than 22% at room temperature.
5. The method for preparing the molybdenum alloy according to any one of claims 1-4, characterized in that, The preparation method of the molybdenum alloy includes the following steps: Step 1): After mixing ammonium molybdate, ammonium tungstate, rare earth yttrium salt, zirconium salt and water, heat and stir to promote the dissolution of ammonium molybdate, ammonium tungstate, rare earth yttrium salt and zirconium salt to obtain a precursor solution; Step 2): The precursor solution is heated to precipitate the complex precursor, and then dried to obtain a mixed powder; Step 3): The mixed powder is calcined to obtain doped molybdenum oxide powder; Step 4): The doped molybdenum oxide powder is reduced under a reducing atmosphere to obtain molybdenum powder; Step 5): The molybdenum powder is sintered to obtain the molybdenum alloy; In step 4): Under a hydrogen reducing atmosphere, the doped molybdenum oxide powder is heated to 520℃-680℃ and held for 1h-3h, and then heated to 700℃-850℃ and held for 2h-6h to carry out reduction treatment to obtain molybdenum powder; wherein the particle size of the molybdenum powder is 300nm-2000nm. During the reduction process: The reduction process is carried out in a hydrogen furnace, wherein the thickness of the doped molybdenum oxide powder in the reduction boat is 3mm-5mm. During the reduction process, molybdenum powder is continuously deposited on the surface using nano-oxide particles as nucleation sites, resulting in a core-shell structure of molybdenum powder with oxide particles as the core and molybdenum powder as the shell; wherein, the oxides include rare earth oxides and zirconium oxide; W element is dissolved in molybdenum powder.
6. The method for preparing the molybdenum alloy according to claim 5, characterized in that, In step 1): the ammonium molybdate is any one or more of ammonium dimolybdate, ammonium tetramolybdate, and ammonium heptamolybdate; the ammonium tungstate is ammonium paratungstate and / or ammonium metatungstate; the rare earth yttrium salt is yttrium nitrate and / or yttrium acetate; and the zirconium salt is nitrate and / or acetate.
7. The method for preparing the molybdenum alloy according to claim 5, characterized in that, In step 2): After filtering the precursor solution to remove impurities, citric acid is added dropwise to adjust the pH value to 1-3 to clarify the liquid. Then, the liquid is heated to precipitate the complex precursor. After drying the complex precursor, the mixed powder is obtained.
8. The method for preparing the molybdenum alloy according to claim 7, characterized in that, In step 2), the temperature of the heat treatment is 65℃-85℃, and the heat treatment time is 10min-30min.
9. The method for preparing the molybdenum alloy according to claim 7, characterized in that, In step 2), the drying process is either spray drying or freeze drying.
10. The method for preparing the molybdenum alloy according to claim 5, characterized in that, In step 3), the calcination temperature is 450℃-600℃, the calcination atmosphere is air or oxygen, and the calcination time is 1h-3h.
11. The method for preparing the molybdenum alloy according to claim 5, characterized in that, In step 5): The molybdenum powder is heated to 1000℃-1100℃ and sintered for 0.5h-1.5h, then heated to 1150℃-1350℃ and sintered for 1h-3h, then heated to 1400℃-1600℃ and sintered for 2h-5h, and finally heated to 2050℃-2150℃ and sintered for 4h-8h to obtain the molybdenum alloy; wherein the sintering pressure is 20MPa-50MPa.
Citation Information
Patent Citations
Lanthanum oxide doped molybdenum-tungsten alloy and preparation method thereof
CN117821794A
Multi-component composite oxide dispersion strengthened molybdenum alloy and preparation method thereof
CN121802260A